Variación de los ingresos tributarios en el departamento de rentas del GAD Municipal del Cantón Vinces durante los períodos 2020-2021. - Medina Arias, Cristhoffer Walter (2022)
Today the slowdown in productivity, digitization, relevance of intangible assets and market concentration create challenges, but also opportunities to improve the monetary system for sustainable growth. The lack of management and control of municipal taxes whose collection is in charge of the GAD de Vinces revenue department represents a low level of income, so that institution does not achieve its complete financial autonomy. The purpose of this case study is to analyze the efficiency in the collection of municipal tax contributions by evaluating these revenues in the institution. The general objective of this research work is to "Analyze the variation in tax revenues of the Municipal GAD of the Vinces canton through the evaluation of the taxes obtained in the Revenue Department during the periods 2020 -2021". To achieve this, the quantitative and qualitative methodological approach is used, using the interview as a research tool to collect all the information and acquire the relevant answers, applying as a data collection instrument a questionnaire of open questions that allow demonstrating the application of the rules and identify the risk of the income area. Consequently, thanks to the results obtained, it was possible to identify the taxes obtained in the revenue department through the analysis of the budgetary documents of the institution during the periods analyzed, thus determining that the collection of taxes is deficient in its collection.